Cyclodextrin Glycosyl Transferase and its application in industries - Budiasih Wahyuntari (Jurnal Teknologi dan Industri Pangan, 2005)
Cyclodextrin glycosyl transferase (CGT-ase) is mainly produced by Bacilli. Systematical name of the enzyme is E.C. 2.4.1.19 -1,4 glucan-4-glycosyl transferase. The enzyme catalyzes hydrolysis of starch intramolecular, and intermolecular transglycosylation of -1,4, glucan chains. Cyclodextrins are -1,4 linked cyclic oligosaccharides resulting from enzymatic degradation of starch by cyclodextrin glycosyl transferase through untramolecular transglycosylation. The major cyclodextrins are made up of 6, 7 and 8 glucopyranose units which are known as -, -, and -cyclodextrin. All CGT-ase catalyze three kinds of cyclodextrins, the proportion of the cyclodextrins depends on the enzyme source and reaction conditions. The intermolecular transglycosylation ability of the enzyme has been applied in transfering glycosyl residues into suitable acceptor. Transglycosylation by the enzymes have been tested to improve solubility of some flavonoids and to favor precipitation ci some glycosides. Keywords : cyclodextrin, cyclodextrin glycosyltransferase